IMPLEMENTASI SISTEM PAJAK ONLINE DALAM PEMUNGUTAN PAJAK DAERAH DI KOTA SEMARANG (Studi pada pajak parkir di Badan Pendapatan Daerah Kota Semarang) - Vashya, Bivelly Anggitha; -, turtiantoro -; Erowati, Dewi - (Journal of Politic and Government Studies, 2022)
The Semarang City Government has made innovations while also utilizing EGovernment by implementing an online system for local tax collection in the City of Semarang, especially on taxes that are paid with a self-assessment system such as parking taxes. This research was conducted in order to find out and analyze the implementation of the online tax system in collecting local taxes in the parking tax sector at the Semarang City Regional Revenue Agency and to determine the supporting factors and inhibiting factors that influence the implementation of the online tax system in collecting local taxes on parking taxes in Semarang. Semarang city. This research is a type of qualitative research using a descriptive approach. The location of the research was carried out at the Regional Revenue Agency of Semarang City. The research subject of Semarang City Regional Revenue Agency and parking tax payers. Data collection techniques were carried out through interviews, observations, and documentation. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. While checking the validity of the data is done by using the triangulation method. The results of this study indicate that the implementation of local tax collection on parking taxes using an online system for monitoring, reporting, and payment has not been going well. The supporting factors of the implementation of local tax collection in the electronic system-based parking tax sector in Semarang City are adequate human resources and have a good understanding and attitude, adequate facilities and budget, the existence of SOPs and organizational structures as guidelines in carrying out their respective duties. Inhibiting factors such as the lack of socialization so that the lack of information received by parking taxpayers, software that often errors due to system differences, the limitations of inputting online tax payments due to differences in the cut off owned by the Semarang City Bapenda with the cut off owned by the taxpayer